2017
DOI: 10.1016/j.socscimed.2017.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Counting the time lived, the time left or illness? Age, proximity to death, morbidity and prescribing expenditures

Abstract: The objective is to understand what really drives prescription expenditure at the end of life in order to inform future expenditure projections and service planning. To achieve this objective an empirical analysis of public medication expenditure on the older population (individuals ≥ 70 years of age) in Ireland (n = 231,780) was undertaken. A two part model is used to analysis the individual effects of age, proximity to death (PTD) and morbidity using individual patient-level data from administrative pharmacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Others have argued that medical technology, rather than proximity to death impacts costs (201,202). In an Irish context, Moore et al found proximity to death, but not age, to be a significant driver of pharmaceutical costs (203), while a Danish study found that pharmaceutical costs will increase with age regardless of proximity to death (204).…”
Section: Age and Proximity To Death Evidencementioning
confidence: 99%
“…Others have argued that medical technology, rather than proximity to death impacts costs (201,202). In an Irish context, Moore et al found proximity to death, but not age, to be a significant driver of pharmaceutical costs (203), while a Danish study found that pharmaceutical costs will increase with age regardless of proximity to death (204).…”
Section: Age and Proximity To Death Evidencementioning
confidence: 99%
“…Hence, there is a pressing need to develop two compartment models which apply the usual factors relating to age for the non‐end‐of‐life component of care and the absolute number of deaths (and its associated volatility) into the end‐of‐life component of care. An excellent example of this approach has been recently applied to prescription costs, and the aIM is eminently suited to modification to achieve this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…What the nearness to death effect observes is that health care demand rises only slowly with age but escalates dramatically as death approaches, irrespective of the age at death . Other measures such as prescription expenditure likewise accelerate as death approaches . Around half of a person's lifetime hospital admissions and bed occupancy are compressed into the last year of life …”
Section: Introductionmentioning
confidence: 99%
“…The link between death and healthcare costs arises from the nearness to death effect, where it is observed that around half of a person's lifetime hospital admissions and bed occupancy occurs in the last year of life [7][8][9][10][11][12][13][14] and more specifically in the last 6 months. 15,16 Indeed, an admission to hospital for medical care (at any age) is associated with a far higher risk of death within 1 year.…”
Section: Introductionmentioning
confidence: 99%